Problem and solution of stock waqf practice in Indonesia: Stakeholder's point of view - Niswah, Farokhah Muzayinatun; Hakimi, Fifi; Fathurochman, Sarrah Fitrianni; Hafizah, Iffah; Indrawan , Imam Wahyudi (Journal of Islamic Economics Lariba, 2023)
IntroductionThe flexibility of the cash waqf enables this Islamic social financial instrument to enter various sectors. Along with technological developments, various forms of cash waqf, such as stock waqf, have emerged. However, stock waqf practices in Indonesia face numerous challenges, leading to limited public awareness. This study aims to identify the primary problems and solutions in the practice of stock waqf in Indonesia.ObjectivesThe objective of this research is to examine the key problems and propose solutions for the practice of stock waqf in Indonesia by leveraging the Analytic Network Process (ANP) for data analysis. MethodThis study combines literature data with in-depth interviews involving stock waqf stakeholders, including the Indonesia Waqf Board (BWI), Indonesia Stock Exchange, waqf issuers, and stock waqf investors. The ANP method was used to analyze the data and identify priority issues and solutions.ResultsThe research reveals that the primary issue in stock waqf practice is low literacy about stock waqf, with the solution being the socialization of stock waqf and enhancing Sharia stock literacy. Additionally, the study identifies the low literacy of productive waqf, public doubts about the sharia compliance of stock waqf, nazir's limited understanding of stock waqf, and the lack of detailed regulations as significant challenges. Corresponding solutions include the socialization of productive waqf, education on Islamic capital market investments, improved nazir training, and the establishment of specific regulations for stock waqf. ImplicationsThe findings suggest that increasing public awareness and education about stock waqf and Sharia stocks, along with better training for nazir and clear regulations, are essential for optimizing the development of stock waqf in Indonesia. This study provides valuable references for BWI and the Indonesia Stock Exchange to enhance the practice and management of stock waqf.Originality/NoveltyThis study offers a comprehensive analysis of the problems and solutions for stock waqf in Indonesia from the perspective of stakeholders. This study contributes to the limited literature on individual stock waqf and employs the ANP method to propose practical solutions for improving stock waqf practices.